Long-term behaviour of complex underground structures in evaporitic rock mass – Experiences gained from calculations and geotechnical observations - Gschwandtner, Gunter G.; Galler, Robert (Tunnelling and underground space technology, 2018)
The assessment of the stability of underground structures is an interdisciplinary effort combining tasks from various special fields. In addition to geotechnical engineering and geology, hydrogeology in particular plays a major role in the determination of long-term behaviour of the structure and the surface area. With regards to the stability of underground structures in evaporitic rock mass, a non-negligible factor is the influence of water, both rainwater and groundwater. The resulting leaching process affects the surrounding rock mass, gradually reducing its strength. The first part of this paper presents an approach for the determination of long-term behaviour of a complex underground structure based on an underground gypsum mine. For this purpose a numerical model was developed, which is based on the geological, hydrogeological and geotechnical conditions, including an implementation of the leaching process. Based on the calculation result a geotechnical monitoring program was developed to observe the long-term behaviour. The second part of this paper presents the aggregated data from a surveying period of four years and compares it with the simulation results. The information gained from the prediction of the long-term behaviour and the regular comparison with the result of the long-term monitoring program can provide a basis for risk evaluation, making it possible to reduce potential risks for the surface area at an early stage, especially in inhabited areas.